PREPOSISI DALAM KITAB ROMA - Sukatan, Jepriarince; Pelealu, Hetty; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTThe title of this research is â€œPreposition in the Book of Romansâ€. This research to identify and classify the forms as well as the meanings of the preposition found in the book of Romans. The research supported by Aarts and Aarts (1982) and Harman (1986). The method used in this research is descriptive method and the data were taken from the book of Romans based on These Holy Bible New King James Version. The result of this research found these are: simple preposition (one-word preposition) consist of: at, in, before, of, between, on, by, since, until, up, from, and with, whereas complex preposition (multi-word preposition) consist of: according to, because of, on account of, in accordance with, and out of. Meanwhile, the meanings of preposition found in this book are: cause or reason, condition, direction, instrument, manner, participation, place, purpose, source, time, respect, level, medium, measurement, and matter. ______________________________________________Key words: Preposition, Form, and Meaning, The Book of Romans in the Bible